Heat and Mechanical Response Analysis of Composite Compressed Natural Gas Cylinders at Vehicle Fire Scenario. (2015) - Ou, K.S.; Zheng, J.; Luo, W.J.; Li, X.F.; Hu, H.S.; Yang, J.B.; Zheng, J.Y.
Abstract: With the worldwide popularization of compressed natural gas (CNG) vehicles, the use of composite cylinders has been growing at a high rate. Due to the flammable composite layers, safety performance of composite CNG cylinders under localized fire exposure caused by accidental vehicle fires has drawn extensive attention. Composite CNG cylinders would be degraded by the fire and even burst before the activation of pressure relief device. In this paper, a comprehensive model is developed for predicting heat and mechanical response of the cylinder subjected to localized fire. Firstly, a three-dimensional computational fluid dynamics (CFD) sub-model is developed for simulating localized fire impingement on the cylinder to obtain heat response data. Secondly, thermophysical and mechanical property degradation of cylinder's aluminum liner and carbon fiber/epoxy composite layers caused by fire is described in detail. Thirdly, a non-linear finite element analysis (FEA) sub-model is developed for predicting mechanical response of the cylinder exposed to fire. Heat response data coupling transfer between CFD sub-model and FEA sub-model is realized to accurately transfer thermo-mechanical boundary condition. Finally, heat and mechanical response of the cylinder subjected to localized fire is studied based on the modeling of a typical composite CNG cylinder. Pressure and temperature of internal CNG slowly rise, and temperature distribution of internal CNG and cylinder's outside surface is uneven during the localized fire. Stress distribution of the cylinder wall is also uneven, and maximum stress is located at the cylindrical shell near the rear head exposed to fire.